CompTIA A+ Core 1 (220-1101) - Bryan, Wes; Wong, Ronnie (Packt Publishing, 2023)
The course begins with a deep dive into the essentials of laptop and mobile device hardware, where you'll learn to identify, use, and connect a wide range of components and accessories. You'll become proficient in distinguishing between different ports, protocols, and networking hardware, grounding your knowledge in practical, real-world IT scenarios. The course focuses on building a robust foundation in wireless standards and networking principles. You'll also gain critical skills in configuring and managing network connections, understanding IP addresses, and mastering internet connectivity nuances. The course wraps up with an essential segment on troubleshooting methodologies. You'll learn to diagnose and resolve common hardware issues, ensuring devices operate smoothly. This end-to-end journey from hardware basics to practical troubleshooting equips you with the skills to tackle a variety of IT challenges confidently. What you will learn Learn network configurations Troubleshoot hardware issues Decode wireless protocols Manage IP and DNS settings Understand cloud services Apply effective troubleshooting Audience Ideal for aspiring IT professionals, this course lays a solid foundation for a career in tech support. Basic computer knowledge is recommended. This course is perfect for those pursuing CompTIA A+ certification as it provides a comprehensive understanding of modern IT infrastructures. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Wes Bryan: Wes Bryan embarked on his IT career path in 2009, initially as a mentored learning instructor, and later transitioning into a technical IT instructor. His exceptional teaching skills were recognized with three global teaching awards for 'Global Technical Instructor' during his early teaching years. Wes has made notable contributions as a member of the CIN (CompTIA Instructor Network) Advisory Board and the Board of Directors for CompTIA AITP (Association of Information Technology Professionals). Certifications: CompTIA A+, Network+, Security+, Server+, Cloud+, CySA+; MCSA; MTA; MCTS; MCP; MS; MCT. Ronnie Wong: Ronnie Wong has had a diverse career, from diesel service and ministry to computer repair and network administration in small businesses. He set up networks and servers and created policies in these roles. As an Edutainer at ITProTV, now ACI Learning, he started as an IT technical instructor, later working as a contract trainer for the University of Florida, Marion County School Systems, and Nationwide Insurance. He provided Cisco, Microsoft Windows, CompTIA, and IT security training to military and DoD personnel. Now the Director of Content Development at ACI Learning, Ronnie's credentials include CCNP Enterprise Infrastructure, CCNA, CompTIA's A+, Network+, Security+, ISC2 CC, CNA Security, and PCNSA.